Nexus between Firm Ownership, Board Composition and Initial Public Offering Stocks Performance at the Nairobi Securities Exchange in Kenya - Okumu, Anaclet Biket; Olweny, Tobias; Muturi, Willy (Journal of Accounting, Business and Finance Research, 2022)
Extant literature has globally demonstrated two anomalies of initial public offering (IPO) stock performance: positive initial returns and long-run underperformance. Kenya’s IPO market is experiencing a downward trend, with the last issue in 2015. The bond market has gained traction compared to the equity market. Studies have associated firm-specific factors with IPO stock performance and ignored the moderating variable of automation. This study analyzed the relationship between firm ownership, board composition and IPO stock performance on the Nairobi Securities Exchange (NSE). The percentage of shares owned by the Kenyan government was used to measure firm ownership, and board composition was measured by the percentage of executive board members to total board members. The performance of IPO stocks was measured using both cumulative abnormal returns (CARs) and buy and hold abnormal returns (BHARs). Automation was measured by IPO stock performance between the pre- and post-automation period. The sample size comprises 15 firms which floated shares between 1994 and 2019, with a total of 2,586 observations. Longitudinal and descriptive study designs were used together with a multiple linear regression to analyze the data. The Hausman test was used to choose between the fixed and random effects models. It was established that both firm ownership and board composition correlated negatively with IPO stock performance. Automation, on the other hand, was positively correlated with board composition but did not correlate with firm ownership. This study will assist the Kenyan government in developing financial stability measures, and investors in making informed decisions.